The relationship between obesity and infertility: A literature review (Research, Society and Development, 2023)
Introduction: The relationship between obesity and infertility has been widely studied. Research shows that obesity can reduce fertility and increase the incidence of pregnancy complications, such as gestational diabetes, pre-eclampsia, premature birth and fetal growth restriction. Objective: To review the current literature on the influence of obesity on fertility, including the possible causes of obesity-related infertility and the effects of obesity on the success of infertility treatments. Methodology: An integrative and descriptive qualitative review is carried out. Results and Discussion: Obesity is a health condition that affects a large portion of the world's population, and is associated with several comorbidities, such as female infertility. The influence of obesity on female infertility is a subject that has been widely discussed in the scientific literature. Final thoughts: In conclusion, obesity is a risk factor for infertility and may negatively affect the success of fertility treatments. Weight loss and the adoption of a healthy lifestyle are essential for the treatment of infertility associated with obesity, but a multidisciplinary and individualized approach is essential for successful treatment. More research is needed to improve understanding of the mechanisms underlying the relationship between obesity and infertility, and to develop more effective strategies for treating this condition.